KEANEKARAGAMAN HAYATI AIR TERJUN TIBU BUNTER – SESAOT SEBAGAI POTENSI EKOWISATA - Muhammad Zulhariadi; R. Didi Kuswara; Mohammad Munzir (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2018)
Lombok is one of the main islands in Indonesia that has a variety of ecosystem types that have the potential to be developed into ecotourism. The purpose of this study is to identify the biodiversity composing the ecosystem of Tibu Bunter Waterfall as one of the potentials of ecotourism. Explorative descriptive research type. The research location is located in Tibu Bunter Waterfall, Pesantek Hamlet in Pakuan Village, Narmada District - West Lombok. The results showed that there were 14 animal species and 21 plant species found around the Tibu Bunter Waterfall. Of the several animal species found, there is one unique species in the Least Concern category based on IUCN RED LIST (2011), namely needle dragonflies with a Calopterygidae pregnancy. In the plant species found there are several types of canopy plants, bamboo species, nail plants, bush plants, herbaceous plants, to mosses. It was concluded that the ecosystem of the Tibu Bunter Waterfall has high biodiversity potential and developed into an ecotourism area.